Report 7: Estimating infection prevalence in Wuhan City from repatriation flights - Thompson,H; Imai,N; Dighe,A; Baguelin,M; Bhatia,S; Boonyasiri,A; Cori,A; Cucunuba,Perez Z; Cuomo-Dannenburg,G; Dorigatti,I; Fitzjohn,R; Fu,H; et al. (2020)
Since the end of January 2020, in response to the growing COVID-19 epidemic, 55 countries have repatriated over 8000 citizens from Wuhan City, China. In addition to quarantine measures for returning citizens, many countries implemented PCR screening to test for infection regardless of symptoms. These flights therefore give estimates of infection prevalence in Wuhan over time. Between 30th January and 1st February (close to the peak of the epidemic in Wuhan), infection prevalence was 0.87% (95% CI: 0.32% - 1.89%). As countries now start to repatriate citizens from Iran and northern Italy, information from repatriated citizens could help inform the level of response necessary to help control the outbreaks unfolding in newly affected areas.